Visualising defects via thermography (DeViz): a combined technological, behavioural and quality systems approach to achieving near zero defect buildings - Goodhew, J; Goodhew, S; Alencastro, J; Fox, M; Killip, G (European Council for an Energy Efficient Economy, 2021)
To achieve carbon reduction targets the emissions from buildings need to be near zero. Thermal defects in buildings pose a significant risk to this goal and contribute to energy performance gaps for space heating. A high-performance building envelope is a fundamental requirement towards meeting emissions targets and providing comfort and affordable warmth. Defects in design and installation (e.g., discontinuity of insulation, incorrect detailing, incompatible building systems) can lead to high rates of heat loss, structural damage from moisture build-up and poor user satisfaction. Many defects are invisible upon completion but can be made visible through the correct use of thermal cameras (thermography).